Reconsidering the Saint-Gilles Shrine and its Description in the Pilgrim’s Guide - Melanie Hanan (Ad Limina)
Although the twelfth-century gold shrine containing the relics of Saint Giles from the abbey of Saint-Gilles in Southern France no longer exists, the lengthy description of it found in Book V, the Pilgrim’s Guide, of the Liber sancti Jacobi allows for its reconstruction. A comparison of both the appearance and use of the Giles shrine to medieval comparanda, including liturgical objects and furniture from Santiago de Compostela described in the Pilgrim’s Guide, reveals not only how unique this reliquary was but also highlights differences between the approaches to relics, worship, and pilgrims at Saint-Gilles and Santiago.